SAW-based radio sensor systems for short-range applications - Scholl, Gerd; Reindl, Leonhard; Ruppel, Clemens; Weigel, Robert (Radio and Wireless Conference, 2003. RAWCON '03. Proceedings, 2003)
Wireless autonomous surface acoustic wave (SAW) sensors offer highest flexibility for modern sensor systems. Because no battery or wiring is required for power-supply and communication tasks they can advantageously be employed for nearly all kinds of short-range identification and measurement applications, where the use of conventional sensors is comfortable, impossible or dangerous, e.g. on moving or rotating parts or in industrial process chambers. In the present work the basics of SAW-based radio sensor systems are reviewed and different examples out of a manifold of possible applications will be given.
elib2cris::1512001600,scholl2003
Keywords: measurement application; radio sensor system; short-range identification; surface acoustic wave sensors; wireless autonomous SAW sensors; surface acoustic wave sensors; wireless sensor networks